GFAP-Positive Neoplastic Astrocytes in Spontaneous Oligodendrogliomas and Mixed Gliomas of Rats. (June 2013) - Nagatani, Mariko; Yamakawa, Seiki; Saito, Tsubasa; Ando, Ryo; Hoshiya, Toru; Tamura, Kazutoshi; Uchida, Kazuyuki
It is generally said that neoplastic cells are immunohistochemically negative for glial fibrillary acidic protein (GFAP) in rat spontaneous astrocytomas, and there are no reports describing the existence of GFAP-positive neoplastic astrocytes in rat spontaneous oligodendrogliomas and mixed gliomas which contain neoplastic astrocytes. In the present study, to clarify whether GFAP-positive neoplastic astrocytes exist in rat spontaneous oligodendrogliomas and mixed gliomas or not, immunohistochemical examination was performed on spontaneous oligodendrogliomas (26 cases) and mixed gliomas (5 cases) collected from the carcinogenicity studies and short-term toxicity studies. The neoplastic cells that constitute oligodendrogliomas and mixed gliomas were morphologically classified into five types: round A, round B, round C, spindle, and bizarre. The cells of round A, B, and C types were thought to be neoplastic oligodendrocytes because of their positive immunostainability for Olig2. The origin of bizarre cells was obscure because they were negative for Olig2, GFAP, and nestin. The spindle cells were considered to be neoplastic astrocytes, because some of them were positive for GFAP or nestin, and GFAP-positive spindle cells could be morphologically distinguished from reactive astrocytes. In conclusion, the present study clarified for the first time that GFAP-positive neoplastic astrocytes exist in rat spontaneous gliomas.